Investigation on mechanical and wear behaviour of AA2024/hBN composites synthesized via powder metallurgy routine. (2021) - Loganathan, P.; Gnanavelbabu, A.; Rajkumar, K.
Abstract: The tribological behaviour of AA2024/hexagonal Boron Nitride (0–7.5 wt% hBN) composites were processed through Powder Metallurgy (PM) routine. The varying wt. % of Al/hBN composites were compacted with help of uni-axial press in a pressure range of 400 MPa and sintered in conventional furnace at 525 °C with argon gas environment. The investigation on theoretical density of alloy and composites of sintered composites increased upto 97%. The optical micrograph of composites reveals fine distribution of hBN particles over the matrix material. The hardness of fabricated samples were characterized with micro Vickers hardness tester its shows increases in hardness upto 68% on (AA2024 + 7.5 wt% hBN) as compare to base matrix (AA2024 + 0 wt% hBN). The wear rate of fabricated samples increased with increasing applied load and sliding velocity. The higher wt. % of hBN composite shows 74.9% of improved wear resistance as compared to base matrix due to formation of lubrication film between the contact zones. The self- lubricating effect of hBN particles reduce coefficient of friction and reduce counter surface material removal rate. The wear mechanism on alloy material was plastic deformation at high load condition and increased wt. % of hBN reveals smooth formation lubricating layer on the surface, and it's acted as an effective protective medium between metal to metal contact.